HbA1c Levels as a Primary Predictor of Diabetic Neuropathy in Patients with Diabetes Mellitus - Satria Akbar Putra Asmara; Ulil Albab Habibah; Ana Fauziyati (FORIKES, 2026)
One of the most common and debilitating long‑term complications of diabetes mellitus is diabetic neuropathy, whose prevalence varies widely across countries. This condition significantly increases the risk of lower‑extremity amputation and diabetic foot ulceration, underscoring the importance of early identification of its predictors. This review aimed to examine recent evidence regarding the association between HbA1c levels and the occurrence of diabetic neuropathy among individuals with diabetes mellitus. A literature search was conducted for articles published between 2015 and 2025 across PubMed, ScienceDirect, and Google Scholar, yielding 12 eligible studies. Of these, eight studies reported a significant association between HbA1c and diabetic neuropathy. Elevated HbA1c levels and wide HbA1c variability were consistently linked to an increased risk and greater severity of neuropathic complications. Longitudinal analyses demonstrated that HbA1c serves as a strong predictor of neuropathy when monitored over time rather than assessed as a single measurement. Moreover, the combination of HbA1c with age and duration of diabetes produced a sensitivity of 78.6% and a specificity of 52.3% (p < 0.0001), indicating enhanced predictive accuracy when these variables are evaluated together. These findings highlight the need for clinicians to assess not only absolute HbA1c values but also HbA1c variability over time to prevent progressive nerve damage. Age and duration of diabetes should likewise be considered essential predictors in evaluating neuropathy risk. In conclusion, this literature review demonstrates that HbA1c is a principal predictor of diabetic neuropathy, reinforcing its critical role in comprehensive glycemic monitoring strategies.Keywords: HbA1c variability; diabetic neuropathy; diabetes mellitus